1991
DOI: 10.1073/pnas.88.8.3407
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of receptor-specific variants of human growth hormone.

Abstract: Human growth hormone (hGH) binds to both the growth hormone (GH) and the prolactin (PRL) receptors. Competition experiments followed by mutational analysis show that the epitope on hGH for hPRL receptor consists of strong determinants in the middle of helix 1 (comprising residues His-18, His-21, and Phe-25), a loop region (including , and the central portion of helix 4 (containing residues Arg-167, Lys-168, Lys-172, Glu-174, . When these residues are mapped on a structural model of hGH, they form a patch that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
94
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(96 citation statements)
references
References 26 publications
1
94
0
1
Order By: Relevance
“…Among those homologous receptors to which HuGH can bind, only two have been cloned, the HuGH-R (10, 11) and the HuPRL-R (12,13), although there are likely to be others such as the receptor for placental lactogen (14). HuGH residues which are critical for binding to either the HuGH-R or HuPRL-R have been identified by analyzing segment-substituted and single residue-substituted HuGH variants, produced by site-directed mutagenesis techniques, with a competitive binding assay using the extracellular binding proteins derived from the receptors (15)(16)(17)(18). Additionally, the variants were used to demonstrate that zinc mediates binding of HuGH to the HuPRL-R (15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among those homologous receptors to which HuGH can bind, only two have been cloned, the HuGH-R (10, 11) and the HuPRL-R (12,13), although there are likely to be others such as the receptor for placental lactogen (14). HuGH residues which are critical for binding to either the HuGH-R or HuPRL-R have been identified by analyzing segment-substituted and single residue-substituted HuGH variants, produced by site-directed mutagenesis techniques, with a competitive binding assay using the extracellular binding proteins derived from the receptors (15)(16)(17)(18). Additionally, the variants were used to demonstrate that zinc mediates binding of HuGH to the HuPRL-R (15).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the variants were used to demonstrate that zinc mediates binding of HuGH to the HuPRL-R (15). Three amino acids ofthe HuGH molecule, residues 18 (His), 21 (His), and 174 (Glu), coordinate with residue 188 (His) of the HuPRL-R to form the four zinc ligands. These zinc ligands appear to be critical for determining the binding preference of HuGH because mutants that alter these positions (15) bind preferentially to somatogenic rather than to lactogenic receptors ( 18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of hPRL are mediated via the PRL receptor (PRLR; Goffin et al 1994) and human GH (hGH) via the GH receptor (GHR; Ultsch et al 1994) and PRLR (Cunningham & Wells 1991, Somers et al 1994. Introduction of a single amino acid substitution into GH and PRL results in analogs that behave as competitive hormone antagonists (Chen et al 1990, Fuh et al 1992, Fuh & Wells 1995, Goffin et al 1996, Ramamoorthy et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The eight substitutions in binding site 1 are H18D, H21N, R167N, K168A, D171S, K172R, E174S, I179T (20,21). It has recently been suggested that the crucial changes are K168A and K172R, both Lys residues.…”
Section: The First Ghr Antagonist: Pegvisomantmentioning
confidence: 99%